Severity and workload related to adverse events in the ICU - Clarita Terra Rodrigues Serafim; Magda Cristina Queiroz Dell'Acqua; Meire Cristina Novelli e Castro; Wilza Carla Spiri; Hélio Rubens de Carvalho Nunes
ABSTRACT Objective: To analyze whether an increase in patient severity and nursing workload are correlated to a greater incidence of adverse events (AEs) in critical patients. Method: A prospective single cohort study was performed on a sample of 138 patients hospitalized in an intensive care unit (ICU). Results: A total of 166 AEs, occurred, affecting 50.7% of the patients. Increased patient severity presented a direct relationship to the probability of AEs occurring. However, nursing workload did not present a statistically significant relationship with the occurrence of AEs. Conclusion: The results cast light on the importance of using evaluation tools by the nursing personnel in order to optimize their daily activities and focus on patient safety.